Not dark yet ebook - Robinson, Peter (Inspector Banks, 2021)
"Robinson is an author with amazing empathy, a snare-trap ear for dialogue, and a clear eye for the telling detail."—Michael Connelly One of the world's greatest suspense writers returns with the 27th novel featuring the legendary detective Alan Banks in the mystery series Stephen King calls "the best now on the market." When property developer Connor Clive Blaydon is found dead, Detective Superintendent Alan Banks and his Yorkshire team dive into the investigation. As luck would have it, someone had installed a cache of spy-cams all around his luxurious home. The team hope that they'll find answers—and the culprit—among the video recordings. Instead of discovering Connor's murderer, however, the grainy and blurred footage reveals another crime: a brutal rape. If they can discover the woman's identity, it could lead to more than justice for the victim; it could change everything the police think they know about Connor and why anyone would want him dead. Meanwhile, tensions are rising between Banks and his friend, Zelda. A super recognizer—able to recognize faces significantly better than most people—Zelda is determined to bring the men who abused her to justice. But stirring up the murky waters of the past will put her in far greater danger than ever before, and Banks worries that he won't be able to stop her from plunging too deep before it's too late.